Analgesic efficacy of intrathecal morphine and bupivacaine during the early postoperative period in patients who underwent robotic-assisted laparoscopic prostatectomy: a prospective randomized controlled study - Shim, Jung-Woo (BMC Urol, 2021)
BACKGROUND: The present study was performed to investigate the analgesic efficacy of intrathecal morphine and bupivacaine (ITMB) in terms of treating early postoperative pain in adult patients who underwent robotic-assisted laparoscopic prostatectomy (RALP). METHODS: Fifty patients were prospectively enrolled and randomly classified into the non-ITMB (n = 25) and ITMB (n = 25) groups. The ITMB therapeutic regimen consisted of 0.2 mg morphine and 7.5 mg bupivacaine (total 1.7 mL). All patients were routinely administered the intravenous patient-controlled analgesia and appropriately treated with rescue intravenous (IV) opioid drugs, based on the discretion of the attending physicians who were blinded to the group assignments. Cumulative IV opioid consumption and the numeric rating scale (NRS) score were assessed at 1, 6, and 24 h postoperatively, and opioid-related complications were measured during the day after surgery. RESULTS: Demographic findings were comparable between patients who did and did not receive ITMB. The intraoperative dose of remifentanil was lower in the ITMB group than in the non-ITMB group. Pain scores (i.e., NRS) at rest and during coughing as well as cumulative IV opioid consumption were significantly lower in patients who received ITMB than in those who did not in the post-anesthesia care unit (PACU; i.e., at 1 h after surgery) and the ward (i.e., at 6 and 24 h after surgery). ITMB was significantly associated with postoperative NRS scores of ≤ 3 at rest and during coughing in the PACU (i.e., at 1 h after surgery) before and after adjusting for cumulative IV opioid consumption. In the ward (i.e., at 6 and 24 h after surgery), ITMB was associated with postoperative NRS scores of ≤ 3 at rest and during coughing before adjusting for cumulative IV opioid consumption but not after. No significant differences in complications were observed, such as post-dural puncture headache, respiratory depression, nausea, vomiting, pruritus, or neurologic sequelae, during or after surgery. CONCLUSION: A single spinal injection of morphine and bupivacaine provided proper early postoperative analgesia and decreased additional requirements for IV opioids in patients who underwent RALP. Trial registration: Clinical Research Information Service, Republic of Korea; approval number: KCT0004350 on October 17, 2019. https://cris.nih.go.kr/cris/en/search/search_result_st01.jsp?seq=15637